Analisis Perilaku Konsumen dalam Pengambilan Keputusan Pembelian Sayur Organik di Kota Medan - Utami, Khairuna; Rauf, Abdul; Salmiah, Salmiah (Universitas Medan Area, 2019)
Research to explain the characteristics of organic vegetable consumers, analyze the decision-making process for purchasing organic vegetables, analyze consumer behavior towards organic vegetables and analyze the relationship between consumer characteristics and consumer behavior towards organic vegetables in July-December 2018. The research area was determined by purposive sampling, namely in the Market Modern Lotte Mart, Transmart Care Shop and Forward Together Pulo Brayan. The number of samples taken is 90 samples. The method of collecting data in this study is primary and secondary. Data analysis used descriptive analysis, Fishbein multi-attribute and Spearman Rank correlation. The attributes studied include; price, taste, nutrient content, color, aroma, freshness, packaging, neatness, durability, shape and size, brand, product quality, and expired information. The results of the study showed that the majority of organic consumers of women aged 31-40 years, work as private employees who have an income level of Rp. 2,000,000-Rp. 3,000,000 per month and have two family members covered. The decision making process for purchasing organic vegetables, consumers have a safe motivation for health by consuming organic vegetables and the realization of a healthy lifestyle into the expected benefits. Organic vegetables have the advantage of freshness attributes, nutrient content, and expired information from other attributes after consuming them. Consumer characteristics do not have a real relationship with consumer behavior towards organic vegetables.